فاعلیة الألعاب الصغیرة المائیة واثرھا على تعلم السباحة الحرة على عینة من طالبات المرحلة الرابعة - مواهب حميد نعمان (الرياضة المعاصرة, 2014)
The importance of research in reliance on scientific concepts to motor learningand see the impact of some of the water sports to achieve educational goals. These methods relying on the principle of the investment of time and effort as a result of follow one of the concepts of transmission of the impact of learning. Thus, helps to speed up the learning.process in the free style swimming and come to learn optimally through playing technigue. Research has demonstrated the problem :- Most of the teachers and trainers traditional instruction methods These methods have adopted lacked of an excitement and thrill of the economy of time and effort, Thus leads to weakness evident in the performance of basic skills for swimming in general and free style swimming is particularly The current researchhas used learning situations similar to the basic skills of swimming free to shape attitudes kinetics similar sequential and scalable difficulty to reach a better learning using educational Aquatics. The Researchaimed preparinagt an educational program using the style of play to teach freestyle in swimming. It is hypothesis the following : There is not statistically significant differences between the experimental and control groups. The experimental group has shown a better learning. The Researchhas recommended that using this programe is making learning faster and better.